Pattern of Education in Pre-Prosperous Families (Case Study in Temenggung Village, Limun District Sarolangun Regency Jambi Province) - Alatas, Uying Hapid; Syukurman, M.; A.S, Fatimah; Tami, Sri; Afrinovera, Afrinovera (Learning Community : Jurnal Pendidikan Luar Sekolah, 2023)
This research is motivated by the behavior of children who are not in accordance with what is expected, such as the behavior of all-powerful, quarrels, ridicule, lack of openness to friends or parents when there are problems and so on. This is presumably because the pattern of education provided by parents is still ineffective, therefore this study aims to find out the description of the application of educational patterns and to find out the obstacles faced by underprivileged parents in Temenggung Village, Limun District, Sarolangun Regency. This type of research is qualitative. Data collection techniques were interviews, observational documentation and sive sampling, and those who became informants were based on criteria, namely parents. The analysis technique used the Milles and Hagerman models, namely data reduction, data display, and data verification. Based on the results of the study, it was found that the pattern of education in children was assigned to the lesser category and never applied to an authoritarian education pattern in children. Based on the results of the study, the researchers made several suggestions, namely: Parents should learn about educational patterns, so that the educational patterns applied by parents can be in accordance with parents' expectations in making their children better. Parents are expected to apply more democratic education patterns so that they can shape and have a better personality in their children. It is hoped that the nagger can see several other factors that have not been studied in this study